Milk compositions of dairy cows with clinical and subclinical intramammary infections - Mahadi, Ida Amalina (2016)
The production and quality of milk can deteriorate by intramammary infections resulting in milk compositions alteration. This study was done to determine the changes in the milk composition parameters and to correlate the relationship between somatic cell counts (SCC) and milk composition parameters of dairy cows with and without IMI. A total of 20 dairy cows from Taman Pertanian Universiti (TPU) and Ladang Angkat (Foster Farms) were included in this study. The California Mastitis Test (CMT) was used to identify subclinical IMI in dairy cows (n=10) while healthy dairy cows (n=10) were used as the negative control based on CMT results (negative, trace) with no clinical signs of IMI. However, no clinical IMI case was found in this study. The SCC and the milk compositions parameters (milk fat, protein, casein, lactose, total solid, solid non-fat (SNF), free fatty acids (FFA), and acidity) were determined and casein, lactose, SNF and SCC were found to be significantly different between control and subclinical IMI groups. Furthermore, casein, lactose and SNF were also found negatively correlated with the SCC. In conclusion, significant changes in milk compositions parameter can be found in milk of dairy cows with subclinical IMI which consequently affect milk quality.